Relationship between Collective Victimhood and Defensive Strategies: Worldviews, Conspiracy Theories and System Justification - Vincze, Orsolya; Németh, Marcell; Amrein-Werner, Hajnalka; Kokorin, Artur; Bigazzi, Sara (Studia Psychologica, 2025)
The current study explores the psychological mechanisms underlying the relationship between collective victimhood beliefs and defensive strategies, including conspiracy theory conditioned on temporality and system justification. Drawing on a sample of 223 participants, the study distinguishes between historical and comparative victimhood beliefs and examines the mediating role of group-level worldviews – specifically distrust, perceived injustice, and vulnerability. Using path analysis, the findings reveal that historical victimhood beliefs are more strongly associated with defensive strategies compared to comparative victimhood beliefs, emphasizing the role of cultural and historical context in shaping these effects. Distrust emerged as a dominant mediator for historical conspiracy theories, while perceived injustice mediated the effect of historical victim beliefs on contemporary conspiracy theories. Notably, vulnerability did not mediate conspiracy theories but was linked to system justification through a negative association. These results underscore the nuanced interplay between collective victim beliefs, worldviews, and defensive strategies, shedding light on the socio-political implications of historical traumas in intergroup relations and public discourse.